Toxicopathological overview of analgesic and anti-inflammatory drugs in animals - C. M. Modi, S.K. Mody, H.B. Patel, G.B. Dudhatra, Avinash Kumar, Madhavi Avale (Journal of Applied Pharmaceutical Science)
Non-Steroidal Anti Inflammatory Drugs (NSAIDs) have been commonly used in both human and veterinary medicine to reduce pain and inflammation in different arthritic and postoperative conditions due to their three major activities, viz., anti-inflammatory, antipyretic, and analgesic. Phenylbutazone, diclofenac, meloxicam and some other NSAIDs are being used as therapeutic measures for pain, inflammation and fever in clinical veterinary medicine. Antiinflammatory effect is mainly due to their ability to inhibit the activities of cyclooxygenases, enzymes those mediate the production of prostaglandins from arachidonic acid, a dietary fatty acid. Cyclooxygenase- 2 (COX-2) is the inducible form of the enzyme and is involved in inflammation. The widespread use of NSAIDs has meant that the adverse effects of these drugs have become increasingly prevalent. The two main adverse drug reactions (ADRs) associated with NSAIDs relate to gastrointestinal (GI) effects and renal effects of the agents. The most common is a propensity to induce gastric or intestinal ulceration that can sometimes be accompanied by anemia from the resultant blood loss. Large variety of compounds with similar actions but varying kinetics in different species thus varying risk of toxicity and variety of toxic effects. Review research relating to these adverse drug reactions, focusing on histopathological findings, which may contribute to the comprehension and possible avoidance of drug-induced disease.
Keywords: Analgesic, Anti-inflammatory drugs, Non-steroidal anti-inflammatory drugs, Toxicopathology.